Economic evaluation of cognitive behavioural therapy for insomnia (CBT-I) for improving health outcomes in adult populations: A systematic review. (December 2020) - Natsky, Andrea N.; Vakulin, Andrew; Chai-Coetzer, Ching L.; Lack, Leon; McEvoy, R.D.; Lovato, Nicole; Sweetman, Alexander; Gordon, Christopher J.; Adams, Robert J.; Kaambwa, Billingsley
Summary: Cognitive behavioural therapy for insomnia (CBT-I) is a promising intervention with established efficacy, yet evidence of its cost-effectiveness remains unclear. Systematic searches were conducted in Medline, Psychinfo, ProQuest, Cochrane, Scopus, CINAHL, Web of Science and Emcare. Titles and abstracts were screened against eligibility criteria, and studies reporting full economic evaluations of CBT-I in adult populations were included and examined in detail. Study characteristics were extracted using a standardised template. Quantitative measures and relevant findings were summarised using a qualitative approach following recommended reporting standards. 1, 168 non-duplicate articles were identified, of which 44 were selected for full-text review. Seven full economic evaluations of CBT-I in adult populations met the inclusion criteria and were incorporated in the final synthesis. Using the dominance ranking framework to compare cost and outcomes, CBT-I was cost-effective compared to pharmacotherapy or no treatment. The limited number of studies included in this review implies that caution should be exercised when interpreting these results. Future studies are encouraged to employ longer time-horizons and larger sample sizes to enable better determination of sustained cost and outcomes changes. Prospero registration number: CRD42019133554.